2016
DOI: 10.1152/jn.00892.2015
|View full text |Cite
|
Sign up to set email alerts
|

ON and OFF inhibition as mechanisms for forward masking in the inferior colliculus: a modeling study

Abstract: Gai Y. ON and OFF inhibition as mechanisms for forward masking in the inferior colliculus: a modeling study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…In a recent study Nelson et al (2009) recorded neuronal activity from the central nucleus the inferior colliculus of awake marmosets, and concluded that forward masking could be better explained in terms of inhibitory mechanisms either in the IC or at lower sites of the auditory pathways. A possible interpretation is that the inferior colliculus might receive inhibitory inputs from the superior paraolivary nucleus (SPON), that would result in a wide dynamic range inhibitory mechanism locked to sound offset (Gai 2016). However, the large variability in forward masking in their dataset makes difficult to reconcile their neuronal threshold shifts with psychophysical threshold shifts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study Nelson et al (2009) recorded neuronal activity from the central nucleus the inferior colliculus of awake marmosets, and concluded that forward masking could be better explained in terms of inhibitory mechanisms either in the IC or at lower sites of the auditory pathways. A possible interpretation is that the inferior colliculus might receive inhibitory inputs from the superior paraolivary nucleus (SPON), that would result in a wide dynamic range inhibitory mechanism locked to sound offset (Gai 2016). However, the large variability in forward masking in their dataset makes difficult to reconcile their neuronal threshold shifts with psychophysical threshold shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition/suppression, neuronal adaptation, inhibition or forward suppression, and offset inhibition are all mechanisms that have been proposed to contribute to simultaneous and non-simultaneous masking (e.g. Duifhuis, 1973; Nelson and Swain, 1996; Oxenham and Moore 1995, 1997; Harris and Dallos, 1979; Brosch and Schreiner, 1997; Gai 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In a recent modeling study of SPON neurons, an ON and OFF inhibition was proposed as a potential mechanism of forward masking (Gai 2016) (note that Gai (2016) used frozen noise as the masker, in contrast to the physiological study conducted by Nelson et al (2009) and the current study, in which the masker was a pure tone at CF). In the Gai study, offset responses of the model SPON (OFF inhibition) were combined with delayed during-stimulus responses of the model DNLL (ON inhibition) to account for observed suppression at the level of the IC.…”
Section: Duration Of Spon Offset Responsementioning
confidence: 81%
“…Inhibition would play an important role in the rate suppression caused by the masker in IC neurons (Nelson et al 2009;Gai 2016). In order to investigate the inhibitory effect of the SPON neuron on the forward-masking paradigm at the level of IC, a model of an IC neuron with a low-pass/band reject rate MTF and a sustained response to pure tones was used as the target of our SPON model responses.…”
Section: Forward Masking In the Icmentioning
confidence: 99%
“…The response of a neuron or a neural circuit to a sustained stimulus can bear three basic features: a response to the stimulus onset (On response), a sustained response as long the stimulus is present, and a response to the stimulus offset (Off response). The On/Off responses are found in neurons of the superior paraolivary nucleus (SPON) of the brainstem, the inferior colliculus (IC) of the midbrain [22], and the auditory cortex [80,4,20]. These On/Off neurons are thought to support functions such as duration selectivity (duration tuning), gap detection, and noise rejection [106].…”
Section: Introductionmentioning
confidence: 99%